China's BRI diplomacy: What it means to India and India's rise - Jagannath P. Panda (OrdnungsPolitisches Portal (OPO), 2021)
Despite the political differences, China and India are in an interdependent trade relationship. Both major powers are each other's largest trading partner. Nevertheless, there is competition between the two countries for supremacy in the Indo-Pacific. India's democratic system and rules-based regulatory policies promote India's rise while standing in the way of China's rise and destabilizing the trade partnership. In addition, the Indian government strongly opposes the BRI. Although competition from the U.S. and India is increasingly pressuring the Chinese government, KpCh is simultaneously responding to the recent Covid-19 pandemic with sovereignty and offering assistance to many countries. That follows Xi's goal to build a strong, sovereign Chinese state that is a global leader and no longer relies on bilateral agreements (such as with India).
Keywords: 330; BRI Diplomacy; India; Foreign Policy